Land Use, Climate Change and Biodiversity Modeling: Perspectives and Applications, 2011, 512 pages - Prasetyo, Lilik Budi (Jurnal Manajemen Hutan Tropika, 2014)
Geographic Information Systems (GIS) is one of the fastest growing technologies. It is hard to resemble definitions of GIS, because it has such a broad application. Principally, it is combining technology and processing capabilities of map and its attributes. One of general definition is a system used to store, manipulate, analyze and display spatial data that has reference to the earth. In the early of its development, GIS is only used for digital mapping for the purposes of resource inventories, cadastral, planning, transportation and census, but by this time GIS has been widely used for modeling and decision making. Along with advances in GIS, remote sensing technology is also increasingly available with different levels of temporal and spatial resolution. Remote sensing data can be used as inputs and spatial modeling validation using GIS. DOI: 10.7226/jtfm.19.3.211